Foster care: concepts and provisions of the law in Malaysia - Nadhilah Binti A. Kadir (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2011)
The study deals with the concept of foster care in Malaysia. Analysis focuses on the concept and provisions of the law on foster care. The law and practices in other countries, including Muslim countries, have also been examined for comparison purposes. This study has embarked on the premise that there is no proper law that regulates foster care in Malaysia. The concept of foster care in Malaysia is examined based on the provisions in the legislation as well as on the practice of the Social Welfare Department. The study has further analysed relevant provisions in Malaysian legislation. References have also been made to the law and practice on foster care in countries like Singapore, United Kingdom and Australia including Muslim countries such as Egypt, Algeria and Bahrain. Islamic law recognizes foster care as kafālah. These comparisons can help to identify the weaknesses of foster care law in Malaysia and as a guideline for improving the law. The study reveals that foster care is one of the means to protect children in need of care and protection. These children require appropriate alternative care for their protection. It is believed that children's welfare is best served in a family setting. This study further proves that the limited provisions on foster care in legislation are not sufficient to govern the foster care system in Malaysia. Finally, the study reveals that the law in Malaysia should be improved by introducing proper legislation and regulations on foster care. It is to be hoped that this study provides increased knowledge about foster care as an appropriate alternative care for children in need of protection in Malaysia.